Exploring the marine ecology from space : experience from Russian-Norwegian cooperation /: experience from Russian-Norwegian cooperation. (2017) - Pozdni︠a︡kov, D. V (Dmitriĭ Viktorovich); Pettersson, Lasse H; Korosov, Anton A
No abstract available